(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This study aims to monitor and identify the role of the Bahrain News Agency (BNA) digital content in shaping Bahraini public opinion regarding the achievements of His Majesty King Hamad bin Isa Al-Khalifa’s reform project. The study aims to measure the impact of BNA’s digital content on public opinion through three main dimensions: the cognitive dimension, the affective dimension, and the behavioral dimension. This descriptive study employs a media survey methodology and was conducted on a random sample of 450 individuals representative of Bahraini society across the Kingdom’s four governorates. The study utilized an electronic questionnaire and its theoretical framework integrates two theories to explain the phenomenon: media dependency theory and media framing theory. The study concludes by revealing the levels of influence across the three dimensions and identifying the most effective digital formats. It also seeks to contribute to the development of a strategic communication plan and the formulation of precisely targeted media messages to protect national achievements and strengthen the identity of the Kingdom of Bahrain.